1994
DOI: 10.1093/ajcp/101.6.761
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Dendritic Cells Have Prognostic Relevance in Hodgkin’s Disease

Abstract: The authors' previous study showed the presence of follicular dendritic cell (FDC) networks--though altered--in neoplastic areas, not only in the nodular lymphocyte predominance type, but also in other types of Hodgkin's disease. The present retrospective study was performed on 102 patients to determine whether the presence or absence of FDC networks, or parts of them, in neoplastic areas has prognostic relevance in Hodgkin's disease. Follicular dendritic cells were visualized with the monoclonal antibody Ki-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 0 publications
2
18
0
5
Order By: Relevance
“…The absence of the meshworks in the lymphocyte-depleted subtype is thought to be due to the loss of the ability of the Hodgkin cells to bind to the FDCs, which as discussed above, are needed for antigen presentation and for B-and T-cell survival, and as a result, progressive break-up of the FDC meshworks may partly be responsible for the lymphocytic depletion [66]. Earlier studies have examined the association of FDCs with the clinical outcome in patients with CHL, and an intermediate prognosis was reported in FDC-positive cases by immunohistochemistry (44% of the cases studied) compared to a guarded prognosis for the FDC-negative cases [67]. Similar results were reported in another study, although it was mainly confined to the nodular sclerosis subtype of CHL, where the authors reported the presence of FDC meshworks, whether intact or disrupted, in about 70% of their cases and that the cases with intact FDC meshworks exhibited relatively better prognosis than those with disrupted meshworks and a much better prognosis than those with absent FDC staining by immunohistochemistry [66].…”
Section: Fdcs In Classical Hodgkin Lymphomamentioning
confidence: 99%
“…The absence of the meshworks in the lymphocyte-depleted subtype is thought to be due to the loss of the ability of the Hodgkin cells to bind to the FDCs, which as discussed above, are needed for antigen presentation and for B-and T-cell survival, and as a result, progressive break-up of the FDC meshworks may partly be responsible for the lymphocytic depletion [66]. Earlier studies have examined the association of FDCs with the clinical outcome in patients with CHL, and an intermediate prognosis was reported in FDC-positive cases by immunohistochemistry (44% of the cases studied) compared to a guarded prognosis for the FDC-negative cases [67]. Similar results were reported in another study, although it was mainly confined to the nodular sclerosis subtype of CHL, where the authors reported the presence of FDC meshworks, whether intact or disrupted, in about 70% of their cases and that the cases with intact FDC meshworks exhibited relatively better prognosis than those with disrupted meshworks and a much better prognosis than those with absent FDC staining by immunohistochemistry [66].…”
Section: Fdcs In Classical Hodgkin Lymphomamentioning
confidence: 99%
“…The secretion of cytokines by neoplastic cells is currently believed to cause the progressive attraction of T cells, histiocytes, plasma cells, and eosinophils, which give rise to nodules replacing the pre-existing follicles and produce the typical pattern of NS-cHL. Within the nodules, there are numerous FDCs, which seem to represent a favourable prognostic indicator [112, 113]. …”
Section: Classic Hlmentioning
confidence: 99%
“…The infiltration of dendritic cells into some primary tumor types has been found to be associated with significantly improved patient survival and a reduced incidence of recurrent disease, indicating an important immune-regulating role for dendritic cells in the local tumor environment. [26][27][28][29][30][31][32][33][34][35] Furthermore, dendritic cells can be used to manipulate immune responses, including those for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%